A Complex Systems Network Approach to Quantifying Peer Effects: Evidence From Ghanaian Preprimary Classrooms. Issue 6 (16th June 2021) - Wolf, Sharon; Gonzalez Canche, Manuel S.; Coe, Kristen
Abstract : Research on classroom peer effects has focused nearly exclusively on high‐income countries and on academic skills. Little is known about peer effects in low‐income countries and whether effects differ under different educational environments (e.g., teacher‐directed versus child‐centered, conditions of concentrated advantage or disadvantage). Based on a data set of Ghanaian preprimary classrooms in the Greater Accra Region collected in the 2015–2016 school year, we use complex system networks with multilevel modeling to study the presence and magnitude of peer effects. Results corroborated small statistically significant effects on academic and nonacademic skills ( d = .06–.10). Peer effects on literacy were larger for children in public schools, who are relatively more disadvantaged than their private school counterparts. Teacher‐directivity intensity did not moderate peer effects.